TINGKAT PERFORMA FISIK DOMINAN ATLET JUDO BLIND (Survei Pada Atlet Papua Pada Peparnas Surakarta 2024): TINGKAT PERFORMA FISIK DOMINAN ATLET JUDO BLIND (Survei Pada Atlet Papua Pada Peparnas Surakarta 2024) - Lestari, Endang Sri; Jariono, Gatot; Nurhidayat, Nurhidayat (Jurnal Porkes, 2025)
The purpose of this study was to determine which physical attributes such as muscle strength, endurance, balance, flexibility, and motor response speed. This research applied a descriptive method with a quantitative approach. The research design adopted the survey method, which is a primary data collection technique by taking direct measurements at the research location. The research population included all 18 Peparnas judo athletes in Surakarta, with the research sample being 18 blind judo athletes in Surakarta, consisting of 12 male athletes and 6 female athletes. Data collection techniques in the form of exams (tests) and physical condition measurements. This research instrument was carried out using questionnaires, interview guidelines, cameras, recorders, pencils, ballpoints, books. The results of the study are the endurance of the MFT test is very good. Percentage of Athlete speed 17% are in the Excellent category, 28% are in the Good category, 11% are in the Moderate category, 33% are in the Less category, 11% are Very Poor. That the speed test is in a moderate state. This value can be explained that the average value of Surakarta City Judo Athletes is 66.7% Very Good, 27.8% Good and 5.5% moderate. The conclusion of this study shows that training focused on increasing muscle strength, balance, and cardiovascular endurance is very important in optimizing the performance of blind judo athletes.